Ecological Jurisprudence and Character Education: A Study of Implementation in the Adiwiyata Program at Madrasahs - Muhammad Anas Maarif; Nur Lailatul Hikmah; Muhamad Arif; Ardianto Ardianto (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
The environmental crisis demands an educational approach that is not only technical but also spiritual and moral. This study aims to analyze the implementation of ecological fiqh in shaping students’ environmental care character at MTs Al Hikam Jombang through the Adiwiyata program. This research employed a qualitative case study design. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using data reduction, display, and conclusion drawing techniques. The findings reveal that ecological fiqh was systematically integrated into the school’s vision, mission, curriculum, learning activities, and institutional culture. Fiqh-based values such as muhasabah (self-reflection), mu’āhadah (commitment), mu‘āqabah (spiritual sanction), muraqabah (awareness of God’s presence), and mujahādah (struggle against ego) were instilled through participatory environmental actions. Students not only gained knowledge of environmental issues but also recognized them as a religious responsibility rooted in the Islamic mandate of stewardship (khalifah) on Earth. This study affirms that fiqh can be reconstructed as a contextual ethical-educational framework, and that Islamic education holds great potential to foster spiritually grounded environmental education.